KNOWLEDGE CONSTRUCTED BY TEACHERS AND INTERNS THAT WORK TOGETHER WITH GROUPS OF ELDERLY PEOPLE (Fiep Bulletin - online, 2013)
One of the settled challenges in our times is the population aging that is occurring in an accelerated fashion, causing redefinitions of roles and actions to support elderly population and, in this context, the professional graduation, leads to the consciousness that is necessary to be continuously building knowledge. Due to that, this study had as its main purpose identify and analyse the knowledge constructed by teachers and interns who works with groups of elderly people, about aging and physical activities in the course of their personal and professional trajectories. This current study has been characterized in a qualitative, descriptive, and interpretative approach by collecting information by semi-structured interview, observations and field journal, having as collaborators 6 teachers and 2 interns working with groups of elderly people in the cities of Novo Hamburgo and São Leopoldo, Rio Grande do Sul. The analysis and interpretation of collected information resulted in The option to work with Aging and Formation; Pedagogic practices in groups of elderly people; and Consolidated knowledge about aging in the academic-professional trajectory, which allowed the understanding of the context, where the interpretations pointed that the work with elderly people occurred by personal choice and/or need on their labor places. The practices keep a same format in the majority of the groups, it means, geared towards movement execution. We have identified that the graduation fails in the aspect of formation in to work with third age people, but it seems to be in some collaborators the desire to learn about this subject. Concluding, we highlight the Physical Education professional must understand the aging process in the social, economic, educational, and health context, to be sure about their role as reality transformation agents.
Keywords: Aging; Formation; Physical Education